2007
DOI: 10.1176/appi.ajp.164.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Development and Clinical Outcome in Attention Deficit Hyperactivity Disorder

Abstract: Decreased volume of the superior cerebellar vermis appears to represent an important substrate of the fixed, nonprogressive anatomical changes that underlie ADHD. The cerebellar hemispheres constitute a more plastic, state-specific marker that may prove to be a target for clinical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 0 publications
6
77
0
1
Order By: Relevance
“…Inclusion criteria included families of European descent with an ADHD proband (age [6][7][8][9][10][11][12][13][14][15][16][17][18]. Exclusionary criteria included prematurity ( < 36 weeks), mental retardation, major medical and neurological disorders, pervasive developmental disorder, psychoses and major mood disorders.…”
Section: Adhd Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria included families of European descent with an ADHD proband (age [6][7][8][9][10][11][12][13][14][15][16][17][18]. Exclusionary criteria included prematurity ( < 36 weeks), mental retardation, major medical and neurological disorders, pervasive developmental disorder, psychoses and major mood disorders.…”
Section: Adhd Populationmentioning
confidence: 99%
“…4,5 Brain studies of patients with ADHD have shown abnormalities in frontal-striatal and cerebellar circuitry. 6,7 Although dopaminergic and noradrenergic medications are clinically effective, 8 animal models provide support for the involvement of additional molecular pathways. 9 Twin studies estimate a heritability of up to 90%, 10 indicating a substantial genetic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…In lobules VIIIA and VIIIB, DAT-IR axons were present in both the external and the internal folia, but the density of immunoreactive axons was greater in the internal folia (Melchitzky and Lewis 2000). Another fMRI study demonstrated that the reduced volume of the inferior posterior cerebellar hemispheres is correlated with a poor clinical outcome in patients with ADHD (Mackie et al 2007). Thus, both the cerebellar vermis and the cerebellar posterior lobe have an important function in motor control (Ito 1984).…”
Section: Role Of Cerebellum In Inhibitory Controlmentioning
confidence: 99%
“…For instance, right parietal cortical normalization accompanied clinical improvement , and progressive volume loss of the inferior posterior lobes of the cerebellum accompanied persistence of ADHD (Mackie et al, 2007). Likewise, persistent ADHD is linked to a progressive loss of hippocampal volume (Shaw et al, 2007b).…”
Section: Mri Of Brain Anatomy In Atypical Pediatric Developmentmentioning
confidence: 99%